2016
DOI: 10.1016/j.jams.2015.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment of a Metatarsus Proximal End Fracture: A Case Report

Abstract: A tuberosity fracture is an avulsion fracture in an area 1.5 cm proximal to the fifth metatarsus. Six to eight weeks of immobilization may be required. A patient with a short leg plaster splint came to our clinic because of pain. The patient had a diagnosis of a fifth metatarsus fracture. Significant edema, fluctuation on the dorsolateral section of the left foot, and red color changes (0.2- to 0.3-cm diameter) on the skin of the anterolateral tibial area of the affected leg were noted. The locations of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…[12,13] Some authors also reported that acupuncture accelerated healing process, resolved edema, and provided analgesia in a case of metatarsal fracture. [14] In conclusion, to the best of our knowledge, this is the first case report to show the effectiveness of acupuncture in the treatment of venous insufficiency and varicose veins. Currently, pharmacological and surgical approaches are commonly used, and our findings are required to be reproduced in further studies.…”
Section: Discussionmentioning
confidence: 67%
“…[12,13] Some authors also reported that acupuncture accelerated healing process, resolved edema, and provided analgesia in a case of metatarsal fracture. [14] In conclusion, to the best of our knowledge, this is the first case report to show the effectiveness of acupuncture in the treatment of venous insufficiency and varicose veins. Currently, pharmacological and surgical approaches are commonly used, and our findings are required to be reproduced in further studies.…”
Section: Discussionmentioning
confidence: 67%